If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + -7d = 29 Reorder the terms: -7d + 6h = 29 Solving -7d + 6h = 29 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-6h' to each side of the equation. -7d + 6h + -6h = 29 + -6h Combine like terms: 6h + -6h = 0 -7d + 0 = 29 + -6h -7d = 29 + -6h Divide each side by '-7'. d = -4.142857143 + 0.8571428571h Simplifying d = -4.142857143 + 0.8571428571h
| y=-6/2-4 | | z/7-4=10 | | x^2+y^2-4x+8y+20=0 | | b+4.003=9 | | 2x-26=8x+13 | | 3(2x*4)+2=4x+50 | | 11(x+1)=20 | | Y=4x/5 | | 48/u=12 | | -10x-5+7x=45 | | 7x+8=5x-6 | | 34(21-6.5x)=16(6x-8)+49.5 | | 2a+5=a-2 | | 1/5-9×/5=3x-7 | | 9n=4-35 | | ln(x)=-1.71636 | | -7v+3(v-5)=-39 | | 8x^2=16x-40/9;x1/3 | | 1-9x/5=3x-7 | | 2=-2(y+3) | | 15x+15y-2xy=0 | | 50+2x= | | -5(2x-19)=2(x-8)-9 | | 2(c+2)+6=5(x-5) | | 125x+1382=284 | | 3(z-4)-1=4(z-5) | | x*ln(x)-2=0 | | 2x^2+30x+99=0 | | y^2-2y-104=0 | | 4x^2-23x-35=o | | 12x+13=21 | | 8(x-2)=-6(x+4)+43 |